The Effect of Service Quality, Customer Trust, And Internet Banking On Customer Loyalty Through Customer Satisfaction - Ika Putri Gaban; Zainul Kisman (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2026)
The rapid digital transformation of the banking industry has intensified competition and shifted customer expectations toward more efficient, secure, and technology-driven services. This study aims to examine the effect of service quality, customer trust, and internet banking on customer loyalty, with customer satisfaction serving as a mediating variable. The research was conducted at PT Bank CIMB Niaga Tbk, Niaga Tower Branch, Jakarta, focusing on customers who actively use internet banking services. A quantitative approach was employed using a survey method, with data collected through structured questionnaires distributed to selected respondents using purposive sampling. The data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results indicate that service quality, customer trust, and internet banking have a positive and significant effect on customer satisfaction. Furthermore, customer satisfaction has a significant positive impact on customer loyalty. Mediation analysis reveals that customer satisfaction plays a crucial mediating role in strengthening the relationship between service quality, customer trust, internet banking, and customer loyalty. These findings highlight the importance of enhancing digital service quality and customer experience as strategic drivers to foster satisfaction and long-term customer loyalty in the modern banking sector.